The Case of Earth's Incredible Shrinking Field. - Mullins, J.
This paper describes how the Earth's magnetic field has been monitored by the use of hidden data in ship logbooks that navigated the planet's ocean during the 16th, 17th and 18th century. The results allowed building a remarkable picture of the earth's magnetic field behavior in the centuries before detailed measurements were possible. It turns out that measurements of the direction of the field relative to the position of the sun were common between 1590 and 1840. By combining these data with the paleointensity measurements to calculate that Earth's field was probably stable prior to 1840, or at least decaying at a much slower rate than it is now
Keywords: Earth incredible shrinking field; Earth magnetic field monitoring; Ocean navigation; Paleointensity measurements; Ship logbooks